Co-infection status of porcine circoviruses (PCV2 and PCV3) and porcine epidemic diarrhea virus (PEDV) in pigs with watery diarrhea in Henan province, central China. (May 2020) - Guo, Zhenhua; Ruan, Haiyu; Qiao, Songlin; Deng, Ruiguang; Zhang, Gaiping
Abstract: Porcine circoviruses (PCV2 and PCV3) and porcine epidemic diarrhea virus (PEDV) are important swine viruses that threaten the swine industry worldwide. Here, we evaluated the co-infection status of PCV2, PCV3 and PEDV in 76 enteric samples from piglets with severe diarrhea disease in Henan, China. All samples were tested by PCR/RT-PCR. Our results showed that the infection rate of PCV2, PCV3 and PEDV was 82.89%, 76.32% and 68.42%, respectively. Interestingly, most of these samples exhibited mixed infections. The co-infection rates of PCV2 and PCV3, PCV2 and PEDV, PCV3 and PEDV were 69.74%, 57.89% and 53.95%, respectively. And the triple infection rate was 48.68%. Furthermore, the genetic characteristics of PCV2 and PCV3 were analyzed based on the cap genes. Two PCV2 genotypes, PCV2b and PCV2d, were circulating in the fields. The cap gene of PCV2b and PCV2d isolates only shared 94.6%–95.0% nucleotide identities. The PCV3 isolates together with the reference strains could be divided into four clades (clade1-4), and the cap genes of these isolates have 98.6%–100% nucleotide identities to each other. Distinctive amino acid substitutions were also characterized on the cap protein of PCV2 and PCV3 isolates. Our studies provide the new knowledge on the co-infectious status of PCV2, PCV3 and PEDV in China. The results also provide insight into the genetic diversity and molecular epidemiology of PCV2 and PCV3. Highlights: High co-infection rate of PCV2, PCV3, and PEDV was determined in pigs with watery diarrhea in Henan province, Central China. Two PCV2 genotypes, PCV2b and PCV2d, were circulating in the fields in central China. PCV3 also exhibits a degree of genetic divergence. Distinctive amino acid substitutions were characterized on the cap protein of PCV2 and PCV3 isolates.